2008
DOI: 10.1080/10615800801950584
|View full text |Cite
|
Sign up to set email alerts
|

Parental support, family conflict, and overprotectiveness: Predicting PTSD symptom levels of adolescents 28 months after a natural disaster

Abstract: The purpose of this study was to evaluate the role of family factors as predictors of posttraumatic stress disorder (PTSD) symptoms among adolescents, a substantial period of time after a natural disaster. It was hypothesized that a lack of parental support, family conflict, and overprotectiveness are all risk factors with regard to levels of PTSD symptoms. A group of 533 schoolchildren and high-school students was investigated 28 months after a huge flood, which was one of the most devastating disasters in Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
117
4
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 39 publications
8
117
4
11
Order By: Relevance
“…Many other factors are related to PTSD and depression, including trauma exposure, age and gender (Kilpatrick et al, 2003; Thabet et al, 2004; Thienkrua et al, 2006). In addition to those variables, some investigations have shown that the parental relationship can affect PTSD or depressive symptoms in children (Bokszczanin, 2008; Dekel & Monson, 2010; Lauterbach et al, 2007). Thus, these variables should be considered when exploring the relationship between PTSD and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Many other factors are related to PTSD and depression, including trauma exposure, age and gender (Kilpatrick et al, 2003; Thabet et al, 2004; Thienkrua et al, 2006). In addition to those variables, some investigations have shown that the parental relationship can affect PTSD or depressive symptoms in children (Bokszczanin, 2008; Dekel & Monson, 2010; Lauterbach et al, 2007). Thus, these variables should be considered when exploring the relationship between PTSD and depression.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of studies examining how social support impacts youth distress post-disaster are correlational and retrospective, and do not include bidirectional models. As an example, Bokszczanin (2008) found that parent social support predicted levels of PTSS among adolescents 28 months after a flood. Assessments in that study were completed at one timepoint only.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, social support may be an important protective factor that buffers children from experiencing significant symptoms of distress (Jieling & Xinchun, 2017; Ma et al, 2011). Inadequate social support is a significant risk factor for PTSS in response to multiple types of disasters, including floods, tornados, hurricanes, earthquakes, fires, and man-made disasters (Bokszczanin, 2008, 2012; Danielson et al, 2017; La Greca et al, 2013). This is an important association among adults as well, as demonstrated by a meta-analysis of risk factors for Posttraumatic Stress Disorder among adults, which found lack of social support to have stronger effects than pre-trauma factors on Posttraumatic Stress Disorder (Brewin, Andrews, & Valentine, 2000).…”
mentioning
confidence: 99%
“…In terms of the existing evidence base, parental overprotection and encouragement of avoidant coping (e.g., avoiding trauma reminders, discouraging trauma-related discussion) have previously been associated with poor child psychological adjustment following trauma (Bokszczanin, 2008; Ehlers, Mayou, & Bryant, 2003; Henry, Tolan, & Gorman-Smith, 2004). Based on cognitive models of PTSD (e.g., Ehlers & Clark, 2000), such coping styles have been hypothesized to increase children’s perception that they are very vulnerable or damaged by the event – a key predictor of poor psychological adjustment (Meiser-Stedman, Dalgleish, Glucksman, Yule, & Smith, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the relationship between maladaptive parenting responses (e.g. overprotection, encouragement of avoidant coping) and child PTSS is more robust (e.g., Bokzczanin et al, 2008; Ehlers et al, 2003); nonetheless, our understanding of the relationship between parenting and child PTSS is hampered by the fact that many studies to date have utilized non-validated measures of post-trauma parenting responses.…”
Section: Introductionmentioning
confidence: 99%